THE DEVELOPMENT OF EMPLOYEE ENGAGEMENT SCALE OF CONVENIENCE STORES IN NORTHERN REGION - Rakjun, Ponkrit; Vannasathid, Prapassorn; Klomthongjarean, Kunpatsawee; Baimai, Chaiwat (Journal of Buddhist Anthropology, 2021)
The objective of this article was to develop an employee engagement scale of convenience stores. This study was a quantitative research. The population was employees in convenience stores in the northern region. The sample size was calculated based on the sample size criteria Hair, et.al The sample size was determined to be at least 20 times per one observable variable. There were 3 observable variables. An appropriate sample size should be at least 60 samples, which was the minimum sample size requirement that could be used for analysis using structural equation model. Copies of questionnaire were sent by the researcher to the Human Resources Manager 200 copies of questionnaire were obtained from the respondents. The response rate was 66.67 The results of this research could be concluded with three stages as follows: Stage 1: the research instrument was adapted from Employee Engagement Scale Bakker et al. The data were translated and adapted to be consistent with the study context. The research instrument consisted of 17 items. Stage 2: Quality of the instrument was improved through content validity with Index of Item – Objective Congruence (IOC) of 0.95 and Cronbach's Alpha of 0.959, implying that the values were acceptable. Stage 3: The analytic results of measurement model revealed parameters as follows: Chi-Square = 0.331, df = 1, p = 0.67, CFI = 1.00, GFI = 1.00, AGFI = 0.99, RMR = 0.008, RMSEA = 0.000, indicating that the Employee Engagement Model was consistent with the empirical data. The findings were consistent with a review of relevant concepts and theories and could be applied for future research on employee engagement in line with the business context.